2022
DOI: 10.1371/journal.pone.0262039
|View full text |Cite
|
Sign up to set email alerts
|

Trophic and symbiotic links between obligate-glacier water bears (Tardigrada) and cryoconite microorganisms

Abstract: Insights into biodiversity and trophic webs are important for understanding ecosystem functions. Although the surfaces of glaciers are one of the most productive and biologically diverse parts of the cryosphere, the links between top consumers, their diet and microbial communities are poorly understood. In this study, for the first time we investigated the relationships between bacteria, fungi and other microeukaryotes as they relate to tardigrades, microscopic metazoans that are top consumers in cryoconite, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 78 publications
(116 reference statements)
2
29
0
Order By: Relevance
“…This study examined the microbiota of the full tardigrade community from a particular substrate sample, in contrast to previous surveys that studied isolated species, often from laboratory cultures ( Vecchi et al, 2018 ; Kaczmarek et al, 2020 ; Mioduchowska et al, 2021 ; Zawierucha et al, 2022 ). While the focus of the current study was the bacteria associated with the full tardigrade community in a given sample, it is of course also desirable to identify species-specific tardigrade microbiota, as Vecchi et al (2018) found that tardigrade-associated bacteria varied among tardigrade species, and we encourage further research on bacteria associated with individual tardigrade species.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This study examined the microbiota of the full tardigrade community from a particular substrate sample, in contrast to previous surveys that studied isolated species, often from laboratory cultures ( Vecchi et al, 2018 ; Kaczmarek et al, 2020 ; Mioduchowska et al, 2021 ; Zawierucha et al, 2022 ). While the focus of the current study was the bacteria associated with the full tardigrade community in a given sample, it is of course also desirable to identify species-specific tardigrade microbiota, as Vecchi et al (2018) found that tardigrade-associated bacteria varied among tardigrade species, and we encourage further research on bacteria associated with individual tardigrade species.…”
Section: Discussionmentioning
confidence: 99%
“…All tardigrade microbiome surveys, including the current study, employed laboratory technique to reduce contamination by washing the tardigrades in sterile water before DNA extraction ( Vecchi et al, 2018 ; Kaczmarek et al, 2020 ; Mioduchowska et al, 2021 ; Zawierucha et al, 2022 ). Working in a sterile environment further decreases contamination; therefore, Zawierucha et al (2022) extracted tardigrades from substrate in a sterile environment (laminar flow chamber), and we worked in a sterile field created by a Bunsen burner throughout the experiment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations